Adoption of Improved Late Sown Mustard Cultivation Practices in Bihar - Sunita Kushwah , Sushil Kumar and A. K.Singh, (Indian Journal of Extension Education, 2016)
Mustard contributes around 23.2 per cent of total oilseed production in India. Attempts are being made to improveproductivity and to increase area under mustard by adoption of HYVs (High yielding varieties). In order to compareconventional mustard with HVY, 65 front line demonstrations were carried out. The demonstrations resultedenhancement in productivity. The yield was found to be increased from 7 (q/ha) in local check to 11 (q/ha) in FLDs.Similarly, the benefit: cost ratio can be further improved to 2.92 as compared to 1.6 in local check. Lack of market andsupport price (93.47) were recorded major constraints in late sown mustard cultivation. Hence increase in yield overfarmer's practices was evident which indicated the need of educating farmers through front line demonstration.